2021
DOI: 10.1177/03915603211049888
|View full text |Cite
|
Sign up to set email alerts
|

The effects of two different antioxidant combinations on sperm parameters

Abstract: Background: Studies demonstrate that getting antioxidants in the course of treatment has a positive impact beneficial effect on fertility, especially on the quality of sperm. Because of that reason antioxidants are recommended as a potentially influential treatment for infertility in men. However, it is argued that this treatment is not based on sufficient evidence and has no effect on the rate of healthy pregnancy. Objective: In this study, two different antioxidant combinations with different doses and conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…[40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure. 34,37 SOD and GSHPx are antioxidant enzymes protecting cells against oxidative damage, and MDA is a oxidation parameter measuring lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure. 34,37 SOD and GSHPx are antioxidant enzymes protecting cells against oxidative damage, and MDA is a oxidation parameter measuring lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some environmental pollutants and viruses induce poor semen quality through increasing levels of oxidative stress . Additionally, antioxidant treatment has been shown to have a positive effect on semen quality . Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure .…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 Drugs commonly used to improve energy metabolism include coenzyme Q 10 and l ‐carnitine, which are often combined with antioxidant effects. 43 …”
Section: Resultsmentioning
confidence: 99%
“…41,42 Drugs commonly used to improve energy metabolism include coenzyme Q 10 and L-carnitine, which are often combined with antioxidant effects. 43 The latest review of 61 included studies indicated that there was insufficient evidence that empiric therapy and nutritional supplements improved semen parameters; moreover, there was insufficient evidence that these methods increased live birth or pregnancy rates. 44 Increasing evidence suggests that improved microcirculation perfusion of the testis can effectively promote spermatogenesis.…”
Section: Metabolic Regulatorsmentioning
confidence: 99%
“…[4,5] Many studies have investigated the efficacy of varicocelectomy on improvement in semen parameters, and several authors have found a significant improvement in semen quality after this surgery. [6][7][8] Although many meta-analyses have shown that all techniques used for varicocele treatment improve sperm parameters, microsurgical varicocelectomy (MSV) is the optimal technique due to its lower rate of complications, such as hydrocele and varicocele recurrence. [9][10][11] According to a metaanalysis by Cayan et al, [12] the rate of hydroceles was significantly lower in MSV (0.44%) than in laparoscopic varicocelectomy (2.84%).…”
Section: Introductionmentioning
confidence: 99%